Could bystander killing contribute significantly to the antitumor activity of brentuximab vedotin given with standard first-line chemotherapy for Hodgkin lymphoma?. (April 2014) - Brown, Michael P; Staudacher, Alexander H
Evaluation of: Younes A, Connors JM, Park SI et al. Brentuximab vedotin combined with ABVD or AVD for patients with newly diagnosed Hodgkin's lymphoma: a Phase 1, open-label, dose-escalation study. Lancet Oncol . 14(13), 1348–1356 (2013). With exceptionally high response rates, the CD30-directed antibody–drug conjugate brentuximab vedotin (BV) was US FDA approved for treatment of patients with relapsed/refractory Hodgkin lymphoma (HL). Now in Phase I clinical trial, it has been shown that combining BV with multiagent chemotherapy (excluding bleomycin) as first-line treatment in HL patients with high-risk disease is feasible. Complete response rates were over 90% and toxicity was manageable. Given that the malignant cell population comprises a minority of HL lesions, and that BV releases a diffusible cytotoxin via a cathepsin B-cleavable linker, we argue that a significant proportion of the antitumor activity of BV can be attributed to bystander cytotoxicity in addition to direct killing of CD30-expressing malignant cells.